Understanding and Modeling the Behavior of Web Map Users - Braga, Vinícius G.; de Oliveira, Welder B.; Rodrigues, Vagner J. do Sacramento; Cardoso, Kleber V. (Journal of Information and Data Management, 2015)
<!–StartFragment–>Geographic Information System (GIS) in general, and Web mapping systems in particular, have become part of our set of digital tools for regular usage similarly to a search engine, an online social network, or a messaging system. However, the literature still lacks works that investigate and model how users interact with these systems. The well-known Web user models are too general, and are unable to accurately represent some specific common actions, such as pan or zoom in a Web mapping system. In this article, we describe how a user interacts with a Web mapping system and present a methodology that we have designed to retrieve this information from a traditional system, the Google Maps. We also develop a synthetic descriptive model of the user’s behavior and we employ this model to create a proof-of-concept workload generator. Finally, we make a performance evaluation with another real-world GIS, called goGeo, to compare our workload generator with a conventional benchmark application. This shows how adding user features can significantly change the effective workload imposed on a GIS, and how this implies that performance evaluations of these systems in the past have often been based on imprecise assumptions.<!–EndFragment–>